2021
DOI: 10.1001/jamacardio.2021.3070
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Transthyretin Amyloid Cardiomyopathy in Heart Failure With Preserved Ejection Fraction

Abstract: IMPORTANCE Heart failure (HF) with preserved ejection fraction (HFpEF) is common, is frequently associated with ventricular wall thickening, and has no effective therapy. Transthyretin amyloid cardiomyopathy (ATTR-CM) can cause the HFpEF clinical phenotype, has highly effective therapy, and is believed to be underrecognized. OBJECTIVE To examine the prevalence of ATTR-CM without and with systematic screening in patients with HFpEF and ventricular wall thickening. DESIGN, SETTING, AND PARTICIPANTS This populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
93
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 24 publications
(44 reference statements)
0
93
0
4
Order By: Relevance
“…History of carpal tunnel syndrome (37%) and spinal stenosis (31%) are common. 5 These extra-cardiac alterations may precede the development of cardiac amyloidosis by many years. The recognition of these signs as part of the clinical picture of amyloidosis is essential, and it may lead to earlier diagnosis and prevent the progression of heart disease through the implementation of specific treatment.…”
Section: Several Clinical Parameters Help Us Consider Amyloidosis;mentioning
confidence: 99%
See 1 more Smart Citation
“…History of carpal tunnel syndrome (37%) and spinal stenosis (31%) are common. 5 These extra-cardiac alterations may precede the development of cardiac amyloidosis by many years. The recognition of these signs as part of the clinical picture of amyloidosis is essential, and it may lead to earlier diagnosis and prevent the progression of heart disease through the implementation of specific treatment.…”
Section: Several Clinical Parameters Help Us Consider Amyloidosis;mentioning
confidence: 99%
“…In a recently published prospective cohort study 5 involving 1235 consecutive patients with validated diagnosis of HF and increased risk of ATTR-CM due to age, HFpEF, and increased LV thickness, the prevalence by clinical recognition was only 1.3%, but it was approximately six times higher (6.3%) in the sample of 286 patients who had signed informed consent for additional tests for systematic screening of ATTR-CM. This evaluation consisted of technetium 99m pyrophosphate scintigraphy and appropriate laboratory exams for ruling out AL amyloidosis.…”
mentioning
confidence: 96%
“…Elucidation of the mechanisms of aging and male propensity of wtATTR will be of importance, as recognition of high prevalence of wtATTR-CA among our aging HF population is increasing with the utilization of noninvasive screening. 13 CRISPR, and RNA interference. Clinical trials.gov was also searched for current or completed trials.…”
mentioning
confidence: 99%
“…Numerous studies performing a systematic assessment of selected patients reported a high prevalence of ATTR-CA with much smaller sex differences. Among patients with heart failure with preserved ejection fraction (HFpEF), 6% to 17% had a diagnosis of ATTR-CA ( 10 , 11 , 12 , 13 , 14 ) including certain patients with severe aortic stenosis ( 15 , 16 , 17 ). A prevalence >20% was repeatedly found in patients older than 80 years of age, with or without HFpEF ( 13 , 14 , 18 ).…”
mentioning
confidence: 99%
“…Among patients with heart failure with preserved ejection fraction (HFpEF), 6% to 17% had a diagnosis of ATTR-CA ( 10 , 11 , 12 , 13 , 14 ) including certain patients with severe aortic stenosis ( 15 , 16 , 17 ). A prevalence >20% was repeatedly found in patients older than 80 years of age, with or without HFpEF ( 13 , 14 , 18 ). Even retrospective studies of unselected patients with bone scintigraphy detected several unexpected cases of ATTR-CA ( 19 , 20 ).…”
mentioning
confidence: 99%